A study comparison of different aggregate between concrete mixture with processed recycled waste and conventional concrete mixture with gravel - Junaidi, Amirul Asyraf; Mahyeddin, Mohd Eizzuddin; Abdul Rahman, Mohammad Ashraf (2021)
This comparison research was developed to compare the performance of concrete mixture that used waste recycled materials as the alternative replacement of coarse aggregate with a conventional concrete mixture that use common granular materials. This is important as different types of materials used in concrete mixture may affect the strength of a concrete. This is due to the nature differences of the material that varies in sizes, grip, endurance, and stability which greatly affects the strength of a concrete mixture. The use of recycled materials in construction industry would greatly affect total waste production. At the end of the comparison, the results shows that the use of recycled materials can be done to replace conventional granular coarse aggregate in concrete mixture.